Thermophysical investigation of glycol ethers in mannitol solutions at various temperatures - Chakraborty Nabaparna; Thakur Priya; Juglan Kailash Chandra; Syed Abrar Hussain (Journal of the Serbian Chemical Society)
Ultrasonic analysis can be very helpful to comprehend the molecular dynamics and interactions in liquid systems. Employing the Anton-Paar (DSA 5000 M) at concentrations and 0.1 MPa, sound speed as well as density of glycol ethers, i.e., phenoxyethanol (PE) and butoxyethanol (BE) in solutions of a well-known sugar alcohol (D-mannitol), were measured at 288.15–303.15 K. A variety of advanced acoustic-thermodynamic parameters, including apparent molar parameters, partial molar parameters and transfer molar properties, were estimated using the experimentally attained the velocity and density values. These derived values are used to express the interactions between solutes and their solvents. The propensity of the solute to generate or destroy structures in a solvent is also a subject of research. Analysis was done on the interactions between the molecules in the ternary mixture of D-mannitol and glycol ethers in aqueous medium.